Analyze of Diagnostic Assessment and Remedial Teaching Result of Mathematics Problem Solving Achievement by Problem Based Learning Model - Hikmasari, Prihatina; Kartono, Kartono; Mariani, Scolastika (Department of Mathematics, Universitas Negeri Semarang, 2017)
This research intents on (1) testing whether the problem solving ability of learners using Problem Based Learning model by using diagnostic assessment and remedial teaching can achieve qualified score; (2) describing the process of appropriate continuation act for learners who cannot pass a test after get learning materials by Problem Based Learning model; (3) describing the result of diagnostic assessment and remedial teaching on ability achievement of problem solving in Mathematics through Problem Based Learning model. This research using mixed methods concurrent embedded. This research using test method, documentation, and interview to take data results. The results of this research showed that (1) the problem solving ability of learners by using Problem Based Learning model with diagnostic assessment and remedial teaching could achieve qualified score was more than 75%; (2) the process to follow up for learners who did not achieve good score after got learning materials by using Problem Based Learning model was carrying out of diagnostic test and remedial teaching; (3) after holding summative test, the researcher got average value 78,97. This case showed us that almost participant of research class got score better than the criteria of specified minimum score.